Pellet culture model for human primary osteoblasts - K Jähn; RG Richards; CW Archer; MJ Stoddart (European Cells & Materials, 2010)
In vitro monolayer culture of human primary osteoblasts (hOBs) often shows unsatisfactory results for extracellular matrix deposition, maturation and calcification. Nevertheless, monolayer culture is still the method of choice for in vitro differentiation of primary osteoblasts. We believe that the delay in mature ECM production by the monolayer cultured osteoblasts is determined by their state of cell maturation. A functional relationship between the inhibition of osteoblast proliferation and the induction of genes associated with matrix maturation was suggested within a monolayer culture model for rat calvarial osteoblasts. We hypothesize, that a pellet culture model could be utilized to decrease initial proliferation and increase the transformation of osteoblasts into a more mature phenotype. We performed pellet cultures using hOBs and compared their differentiation potential to 2D monolayer cultures. Using the pellet culture model, we were able to generate a population of cuboidal shaped central osteoblastic cells. Increased proliferation, as seen during low-density monolayer culture, was absent in pellet cultures and monolayers seeded at 40,000 cells/cm2. Moreover, the expression pattern of phenotypic markers Runx2, osterix, osteocalcin, col I and E11 mRNA was significantly different depending on whether the cells were cultured in low density monolayer, high density monolayer or pellet culture. We conclude that the transformation of the osteoblast phenotype in vitro to a more mature stage can be achieved more rapidly in 3D culture. Moreover, that dense monolayer leads to the formation of more mature osteoblasts than low-density seeded monolayer, while hOB cells in pellets seem to have transformed even further along the osteoblast phenotype.